Performance enhancement of a thin film tungsten oxide based solid-state electrochromic device - Bimal Nepal; Dominic Smith; Dip Dutta; Jacob Hannah; Bikram Bhatia; Sergio B Mendes (Materials Research Express)
Electrochromic devices for emissivity modulation hold immense promise for applications such as thermal management, dynamic optics, and radiative cooling. However, conventional all-solid-state electrochromic devices often suffer from slow switching speeds, limited optical contrast, and challenges in scalable fabrication. In this article, we report on the development and optimization of a high performance all-solid-state electrochromic device that addresses these limitations. The device exhibits significantly faster switching times of 8.2 s (coloring) and 3.1 s (bleaching), compared to the typical switching times of ∼20 s to a few minutes reported for similar solid-state electrochromic devices, marking a key advancement in emissivity modulation technology. Constructed using a stack of thin films—Au/NiO/Ta _2 O _5 /WO _3 /ITO—fabricated through RF magnetron sputtering, the device’s layers were meticulously optimized to reduce resistance while preserving essential optical properties. The device demonstrated a maximum reflectance modulation of about 50%–60% across a broad wavelength range from the visible to the infrared. Its all-solid-state thin-film construction ensures robust performance under high-temperature conditions, demonstrating potential for long-term stability and scalability in practical applications. These advancements position solid-state emissivity control devices as scalable and energy-efficient solutions for dynamic optics, thermal management, and emissivity-based radiative cooling.